Transformation for Survival of Media Organizations in Dynamic Society - Jitprakong, Punyawan (Parichart Journal, 2024)
The purpose of this academic article was to study the transformation of organizations to survive under a dynamic society. This study used mass media organizations as a case study of transformation in order to respond or adapt to changing environmental contexts, values, and fluctuations in information technology. Here, two types of media were selected, namely traditional media and new media. Concerning data analysis, the organizational theory was applied with the two dimensions: organizational goals and an organizational structure which could make the difference visible. The research findings revealed that mass media organizations, both old and new media, needed to be transformed and adapted to survive under environmental fluctuations with information technology elements and changing lifestyles. As a result, media must be structured and operated in a more integrated manner, consisting of determining content, content format, and production or presentation to support new social norms that emphasize the principles of freedom and individuality which has no limitations of space and time. These conditions and elements will lead mass media organizations to survive under the current social context.